Strategi transformasi digital pada lembaga keuangan syariah: inovasi dan kepatuhan syariah - wardani, yuke ivana kusuma (Maliki Interdisciplinary Journal, 2025)
Digital transformation in Islamic financial institutions is a necessity in the era of technological disruption. This process is not only oriented towards efficiency and service innovation, but must also maintain compliance with Shariah principles. This article aims to examine digital transformation strategies in Islamic financial institutions based on a review of literature from various academic sources. The study highlights the synergy between technological innovation, such as Artificial Intelligence (AI), and the implementation of the Shariah Governance Framework as a key pillar in maintaining the balance between technological advancement and Shariah compliance. The results of the study indicate that implementing digital transformation in Islamic financial institutions requires strong governance based on aqidah, Shariah compliance, and ethics (akhlaq-based ethics). Furthermore, the role of humans and organizational culture is an important factor in ensuring the success of sustainable digitalization in accordance with maqashid al-Shariah.